Nucleophilic Interception of the γ,δ-Acetylenic α,β-Olefinic Aldehyde Intermediate Formed from Furil Monotosylhydrazone - Sparrapan, Regina; Kascheres, Concetta; Gambardella, Maria Tereza P. (American Chemical Society (ACS), 1995)
The reaction of furil monotosylhydrazone (1) with nucleophiles under basic conditions led to the formation of 5-(2-furoylmethylene)-2-pyrrolidinones 3 when amines and hydrazine hydrate were used. Treatment with methylhydrazine led to production of 1-methyl-6-(2-furoylmethylene)-pyridazine (4) while treatment with phenylhydrazine and 4-nitrophenylhydrazine produced 1-(2-furoyl)-6-anilino-6-azafulvene (5a) and 1-(2-furoyl)-6-(4-nitroanilino)-6-azafulvene (5b), respectively. All products suggest interception of the γ,δ-acetylenic α,β-olefinic aldehyde intermediate 2 formed via the unstable 1,2-difuryldiazoethanone. © 1995, American Chemical Society. All rights reserved.